Biomechanical considerations of CMJ and SQJ on the safety mat - Nakazawa, M.; Ida, H.; Nakazawa, K.; Aisaka, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to detect whether differences exist concerning the kinematic parameters of jump (SQJ and CMJ) on two different surfaces (RS and SS). Nine healthy students performed two jumps on two surfaces. Two factor repeated measure (ANOVA) was used for statistical analysis (p<.05). No significant difference about GRF was found among all conditions. Fy-anterior on SS was smaller than on FM (p<.05) and Fy-posterior of CMJ was smaller than SQJ on RS (p<.05). Kinematic analysis revealed significant differences in the angle of ankle between SS and FM during starting posture (p<.05). It became clear that knee joint angular velocity is significantly faster on RS than SS (p<.05). In conclusion, by riding on SS, the significant difference seen by SQJ and CMJ of RS had disappeared.